Karakter yang Diperlukan Dunia Kerja dalam Menghadapi Pasar Bebas Asean 2015 - Tirtawinata, Christofora Megawati (Bina Nusantara University, 2014)
ASEAN Free Trade will be started in 2015 and at that time global competition, especially between the countries of ASEAN would be more competititive. In ASEAN free trade area, every country in ASEAN could not simply disallow the incoming of foreign workers. Companies will be filled by workers from various countries, especially workers from ASEAN countries. Not only the government should prepare everything to face the ASEAN Free Trade, but also the working-age individuals need to prepare themselves to get involve in this competition. Preparation should be done by an individual in addition to being competent in his field, an individual also must have an adequate understanding of cultural diversity and its impact on a person's personality as well as how to deal with cultural diversity and challenges. Therefore, it takes a certain individual to the character to be able to work together with people with different cultures. This article was prepared based on need, using empirical observations and experience, as well as library research to answer all the problems that will confront every individual working age in the era of ASEAN Free Trade.